EFFICACY OF SUB-TENON'S BLOCK IN PAEDIATRIC STRABISMUS SURGERY IN TERMS OF REDUCTION IN OCULOCARDIAC REFLEX - Noor ul Hussain,; Muhammad Naeem Khan, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Strabismus is a common disease entity in paediatric age group usually requiring surgical intervention under general anaesthesia and Oculocardiac reflex is the most dangerous complications intraoperatively. Various anaesthetic options have been evaluated to mitigate this complication. The objective of this study was to assess the efficacy of sub-tenon's block in paediatric strabismus surgery in terms of reduction in oculocardiac reflex. Methods: This prospective Randomized control trial was conducted at Department of ophthalmology, MTI, Hayatabad Medical complex, Peshawar over a period of six months from 1st July to 31st December 2021. A total of 124, were equally divided in sub-tenon's group (Group A) and placebo group (Group B). Intraoperatively, patients were assessed for Bradycardia and development of OCR. Data including demographics, intraoperative BP, HR and OCR development were noted and analysed with SPSS version 22. Results: The total number of patients were 124, 62 in each group with a mean age of 9.45±1.61. Sixty-six (53.22%) patients were males and 58 (46.87%) patients were females. At 10-, 20- and 30-minutes interval, the SBP and DBP has no significant difference. At 10, 20, 30 minutes interval, the HR differed significantly (79.33±7.36 vs 66.65±6.83 (pË‚0.05), 79.78±7.63 vs 66.57±7.06 (pË‚0.05), 79.80±7.78 vs 66.52±7.01 (pË‚0.05), respectively. Intraoperative OCR was recorded in 13 (21%) patients in sub-tenon's (Group A) versus 56 (90.30%) patients in placebo (Group B) with statistically significant difference between the two (p<0.05). Conclusion: Sub-tenon's injection of bupivacaine reduces the incidence of Bradycardia and OCR in squint surgery patients after general anaesthesia induction and usage is recommended in routine.